2021
DOI: 10.1177/08862605211064239
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Test of the Impact of Varying Questionnaire Response Format on Prevalence Rates for Sexual Violence Victimization and Perpetration

Abstract: Objective: This study examined the impact of a dichotomous versus scaled response format on prevalence rates of sexual violence perpetration and victimization, thus conceptually replicating Hamby et al., 2006 and extending those findings to the context of sexual violence. Methods: Two samples were recruited from Amazon Mechanical Turk and were randomly assigned to either a dichotomous or scaled response format of the same questionnaire. Sample 1 was used to examine perpetration and received a perpetration spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 60 publications
(84 reference statements)
4
11
0
Order By: Relevance
“…However, in combination these effects appear greater, as suggested by the 15.75% average sexual assault acknowledgment rate. These findings are consistent with other studies suggesting a scaled response format increases affirmative responding for both perpetration (Anderson & Cuccolo, 2021; Hamby et al, 2006) and victimization experiences (Hammond & Calhoun, 2007; Peterson & Muehlenhard, 2011). Although the exact mechanism is unclear, especially when comparing reporting perpetration versus victimization, it is likely that by providing a large numerical range, participants infer that disclosing perpetration behaviors is at least somewhat normative.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, in combination these effects appear greater, as suggested by the 15.75% average sexual assault acknowledgment rate. These findings are consistent with other studies suggesting a scaled response format increases affirmative responding for both perpetration (Anderson & Cuccolo, 2021; Hamby et al, 2006) and victimization experiences (Hammond & Calhoun, 2007; Peterson & Muehlenhard, 2011). Although the exact mechanism is unclear, especially when comparing reporting perpetration versus victimization, it is likely that by providing a large numerical range, participants infer that disclosing perpetration behaviors is at least somewhat normative.…”
Section: Discussionsupporting
confidence: 91%
“…Given these pressures, Peterson and Muehlenhard (2004) suggest using a scaled response format to measure acknowledgment. Anderson and Cuccolo (2021) found that, without changing the wording of the items, randomly assigning participants to a scaled response format instead of a dichotomous (yes/no) increased reported perpetration behavior on the order of 1.7-9x more cases identified. Hamby et al (2006), focusing on intimate partner sexual perpetration, found similar results-in a scaled response format condition, prevalence rates were 3x higher than the dichotomous condition (7.5% vs. 22.5%).…”
Section: Response Formatmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it presents five screening scenarios that state either an act or tactic: victimization by voyeurism (i.e., an act; e.g., “How many times in your lifetime has someone: spied on you, taken photos, or recorded a video of you for their own sexual gratification without your consent or permission?”), nonconsensual touching (i.e., act), verbal coercion (i.e., tactic), being used as a passive sexual object (i.e., act), and being physically forced to have sex with another person (i.e., tactic). The wording and format of the SEQ was influenced by the SES (Koss et al, 2007) but was amended to present a broader frequency scale (0, 1, 2–5, 6–9, 10+ rather than 0, 1, 2, 3+) and includes items related to perpetration by women, victimization of men, and CSA, with the initial screening question being in a broader scaled format than the SES, as suggested by Anderson and Cuccolo (2022). Follow-up questions for each scenario ask how old the respondent was the first time an experience of this type occurred, with remaining questions pertaining to the most recent time it occurred, the gender of and relationship to the perpetrator, and questions about the nature of the assault itself.…”
Section: Methodsmentioning
confidence: 99%
“…The use of behaviorally specific questions may be the most effective means of measuring sexual violence, particularly if the respondent only needs to answer a direct closed question, rather than voluntarily provide information to an open question (Krebs, 2014; Krebs et al, 2021). In addition, the use of a broad-scale response format, where respondents are asked how many times a specific behavior has occurred rather than whether it has happened, has also been found to maximize response rates among men, and victims of verbal coercion generally (Anderson & Cuccolo, 2022).…”
mentioning
confidence: 99%